Evaluation of mechanism of change in transdiagnostic cognitive behaviour therapy using single case experimental design. (June 2021) - Sighvatsson, Magnus Blondahl; Salkovskis, Paul M.; Sigurdsson, Engilbert; Valdimarsdottir, Heiddis B.; Thorsdottir, Fanney; Sigurdsson, Jon Fridrik
Abstract: Background and objectives: Transdiagnostic mechanisms of change (txMOC) specific to cognitive behaviour therapy are poorly understood. Salkovskis (1996) proposed one such mechanism in terms of the shift towards an alternative, less negative view of their problems or cognitive flexibility. This hypothesis has been described as involving a shift in beliefs, from "theory A″ to "theory B". The objective of this research was to evaluate this hypothesis. Methods: Effectiveness of a novel txCBT and temporal changes in process and symptom measures were evaluated using a non-concurrent multiple baseline design and Tau- U calculations with thirteen participants (five with obsessive-compulsive disorder, two with panic disorder with agoraphobia and six with major depressive disorder). As a secondary analysis authors calculated Kendall's – Tau correlation between process and symptom measures, performed the Wilcoxon signed-rank test to assess treatment modules effect on negative thought and calculated Reliable change index (RCI). Results: The txCBT was clearly effective for eight participants. The results varied dependent on the stimuli evaluated as negative or threatening. Level and trend of the ratings of belief in theory A followed the level and trend of symptom measures to a greater extent than the (inverse) level and trend of belief in theory B. Limitations: Only thirteen participants were recruited and evaluated. Conclusions: The results are consistent with the view that effective treatment may involve a txMOC characterized by the ability to shift from a relatively fixed negative view of their experience to a less negative psychologically focused alternative. Highlights: Novel transdiagnostic CBT was effective for eight of thirteen participants. Cognitive flexibility was evaluated as a hypothesized mechanism of change. Decreased symptomalogy was associated to cognitive flexibility. Effectiveness was modereted by the theme of negative and/or threat based thought. Cognitive flexibility was not dependent on modules provided in the treatment.